((The effect of climate on the spread of whooping cough disease in Maysan Governorate for the period (2001-2020(( (Journal of the College of Basic Education, 2023)
Climate, with its basic elements (solar radiation, temperature, wind, air humidity and rain), is the most important component of the natural environment in which man lives, because of its effective impact on human health and various activities and infection with endemic diseases through its direct impact on pathogens and their vectors of insects and the reproduction of parasites and germs And viruses and in the proliferation of organisms that transmit diseases or store their microbes, as these favorable climatic elements provide ideal conditions for pathogens, especially whooping cough. Through the study, it was shown that whooping cough disease could appear in the study area as a result of the spread of swamps, marshes and stagnant water